UPAYA KONSERVASI TANAH PADA PETANI DENGAN DAN TANPA TERNAK RUMINANSIA DI DAS SERANG BAGIAN HULU, KABUPATEN BOYOLALI - Joko Triastono; Sri Widodo; Irham Irham; Suhatmini Hardyastuti (Jurnal Dinamika Sosial Ekonomi, 2005)
Soil erosion represent the main factor on land degradation, especially in upper watershed area. Therefore, soil conservation effort must be done on agricultural land to maintain soil productivity. The objectives of this research are to know the level of knowledge, attitude and behavior of farmer in soil conservation and to estimate factors influencing of farmers in soil conservation activity. The research used a cross-sectional data of 197 sample farmers consisted of 86 farmers with livestock and 111 farmers without livestock. The method of data analysis used t-test and regression with Ordinary Least Square (OLS). The results show that the level of knowledge, attitude and behavior of farmers at farmers with livestock are higher than farmers without livestock. Factors influencing farmer activity on soil consenvation are level of knowledge and attitude in soil conservation activities, farmer education and livestock enterprise.Key Words: Soil Conservation, Farmer Education, Livestock Enterprise